Questions of Education and Psychology - Kiselev A. A., Zabashta R. V., Anin S. A., Belousov V. A., Darovskikh I. E., Pervukhin D. V., Eyeberdiyeva M. K., Sudakov D. V., Shevtsov A. N., Belov E. V., Sudakov O. V., Bogacheva E. V., Muratova O. I., Tochilina I. N., Tabachuk N. P., Godzhaeva N. S., Tochilina I. N., Golovach V. M., Krivushina O. A., Potapova A. V., Lastkov D. O., Klimenko A. I., Mikhailova T. V., Romanenko T. A., Obornev A. L., Sudakov D. V., Sudakov D. V., Sudakov O. V., Nazliev D. K., Belov E. V., Bogacheva E. V., Belov E. V., Sudakov O. V., Shevtsov A. N., Shevtsov A. N., Muratova O. I., Larina E. A., Zhizhina M. V. (Questions of Education and Psychology, 2020)
the article discusses the possibilities of forming partnerships in the “school – university” educational system, the features of the development of extended cooperation on the example of a model made in the IDEF0 notation, which is widely used in world practice. Possible ways to optimize approaches and planning of the educational process that would meet the latest trends of educational standards are analyzed. The problem of the need to introduce new pedagogical practices, which is caused by a change in the functional approach, is considered. Various methodologies and practices of process and project management that have the advantage of multi-level activity decomposition are analyzed. The graphical language and visualization of which helps to form a detailed representation of the overall picture for the full implementation of the tasks set. The purpose of the presented process model is to establish network partner relations between schools and universities. The step-by-step, waterfall process model proposed in the article clearly demonstrates the amount of resources needed and determines the step-by-step process of project implementation. The considered possibility of establishing partnership relations is aimed at attracting potential University applicants. The awakening of academic interest among potential applicants is formed through the use of various activities on the part of the educational institution and the activity team.
Keywords: управление проектом; процессные модели; каскадная методология; анализ моделей; нотации IDEF0; process models; project management; waterfall methodology; model analysis; IDEF0 notation